Regeneration failure and seedling growth of Dipterocarpus gracilis, a vulnerable dipterocarp in a tropical monsoon forest in Central Java, Indonesia - NESTY PRATIWI ROMADINI; SAPTO INDRIOKO; WIDIYATNO WIDIYATNO; ENY FARIDAH (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Romadini NP, Indrioko S, Widiyatno, Faridah E. 2022. Regeneration failure and seedling growth of Dipterocarpus gracilis, a vulnerable dipterocarp in a tropical monsoon forest in Central Java, Indonesia. Biodiversitas 23: 4928-4939. Dipterocarpus gracilis Blume is a vulnerable native dipterocarp species on Java Island, Indonesia. Yet, limited understanding regarding its regeneration capacity in its natural habitat is available to support a sustainable population. The research aimed to investigate the survival and growth of D. gracilis seedlings across canopy openness (CO) in Kecubung Ulolanang Nature Reserve, Central Java, Indonesia. After 10 months of observation, the highest survival rate was found in CO >20%-25% (44%), and the lowest survival rate was observed in CO <15%-20% (20%). The highest relative growth rate of height (RGR H) and the relative growth rate of diameter (RGR D) were found in CO >20%-25% (1.03 ± 0.03 cm and 1.87 ± 0.03 mm). CO <15% showed the lowest RGR H and RGR D (0.6 ± 0.02 cm and 1.39 ± 0.02 mm). The RGR H and D showed a significant CO >20%-25% increase compared with other canopy classes. Pearson’s correlation between RGR D and CO was 0.466 (p >0.05). Our observation indicated that dry months were a critical period for seedling survival. This study showed poor regeneration capacity of D. gracilis, implying that failure in a seedling establishment over time would alter the tree demographics of D. gracilis.